TEACHERS QUESTIONING STRATEGIES IN ACHIEVING STUDENTS SPEAKING COMPETENCE IN ENGLISH CLASSROOM - Mohammad Yasid; Ahmad Munir; Pratiwi Retnaningdiyah (Universitas Islam Negeri Alauddin Makassar, 2021)
The study investigates the grilling system teachers applied at school to know the learners’ answers and “the” teachers’ reasons for achieving students’ speaking competence in English classrooms. The qualitative method is chosen to see the researcher's question responses, the observation in the classroom, and some questions toward the educators. As the findings implied, the two teachers required prompting, changing cognitive demand levels, and providing additional information in display type more dominant than others questions strategies and effective communication. The teacher at the private school repeated the questions and translated them into Indonesia or mixed the questions to relieve the learners' understanding about inquiries and responses effectively. Nevertheless, the totality of English was engaged by the teacher at the state school. The students were easier to understand simpler after the teacher explores many questions and applied much longer time toward the wait time method. The study presented the helpful results of the questions used when the teachers operated in the teaching and learning process and upgraded learners' responses in participating in the learning process. This study offered effective teachers’ questioning strategies in increasing learners' communicative skills, particularly in achieving speaking competence.